Relevance of Meta Tags and Search Engine Optimisation (SEO) Strategies in Web Localisation - Álvarez-García, Carmen (Íkala, Revista de Lenguaje y Cultura, 2025)
Search engine optimisation (SEO) aims to improve the visibility, volume, and quality of traffic to a website or a webpage in search engines. This leads to the idea that web localisation also requires approaching the translation and adaptation of SEO into the target language and market. The main objective of this study is to explore the use and content of three key meta tags: tag, header tags, and the attribute description, embedded in the <meta content> tag, on the English-localised websites of a corpus of 88 Spanish firms with geographical indications approved by the European Commission. To this end, a corpus of 480 webpages was created and analysed both manually and using the corpus tool Sketch Engine. The main results show that the companies analysed perform well regarding tags or tags, while the description attributes have room for improvement. Although, in general, the English localisation of the analysed elements needs improvement; it has been found that most of the analysed companies could benefit from greater attention to mentions of geographical indications in both their Spanish websites and their corresponding English-localised versions.